Revision of the New Zealand endemic genus Pseudoscelolabes Collin (Diptera: Hybotidae: Ocydromiinae) - Barros, Luana Machado; Soares, Matheus Mickael Mota; de Freitas-Silva, Rafael Augusto Pinheiro; Sinclair, Bradley J.; Ale-Rocha, Rosaly (Zootaxa, 2022)
Pseudoscelolabes Collin, 1933, an endemic New Zealand genus, is revised, including the description of a new species, P. lesagei Sinclair & Barros sp. nov. The male and female terminalia of the genus are described and illustrated for the first time. An identification key to the two included species and a map with distribution records are provided. The relationships of the genus within Ocydromiinae are discussed.